Efficacy and safety of tocilizumab in giant cell arteritis: a single centre NHS experience using imaging (ultrasound and PET-CT) as a diagnostic and monitoring tool. Issue 3 (7th November 2020) - Sebastian, Alwin; Kayani, Abdul; Prieto-Pena, Diana; Tomelleri, Alessandro; Whitlock, Madeline; Mo, Jonathan; van der Geest, Niels; Dasgupta, Bhaskar
Abstract : Tocilizumab (TCZ), an IL-6 receptor blocker, is approved for relapsing, refractory giant cell arteritis (GCA). We report real-life clinical experience with TCZ in GCA including assessment of responses on imaging (ultrasound (US) and 18F-Fluorodeoxyglucose Positron Emission Tomography-computed Tomography ( 18 FDG-PET-CT)) during the first year of treatment. We included 22 consecutive patients with GCA treated with TCZ where EULAR core data set on disease activity, quality of life (QoL) and treatment-related complications were collected. Pre-TCZ US and 18 FDG-PET/CT findings were available for 21 and 4 patients, respectively, where we determined the effect on US halo thickness, temporal and axillary artery Southend Halo Score and Total Vascular Score on 18 FDG-PET-CT. The 22 patients with GCA (10 cranial, 10 large vessel, 2 both) had a median disease duration of 58.5 (range, 1–370) weeks prior to initiation of TCZ. Half had used prior conventional synthetic disease-modifying antirheumatic drug (csDMARDs). TCZ was initiated for refractory (50%), ischaemic (36%) or relapsing (14%) disease. Median follow-up was 43 (12–52) weeks. TCZ was discontinued due to serious adverse events (SAEs) in two patients. On treatment with TCZ, 4 discontinued prednisolone, 11 required doses ≤2.5 mg, 2 required daily dose of 2.5–5 mg and 5 needed prednisolones ≥5 mg daily. QoL improved by 50%. Total US halo thickness decreased in 38 arterial segments, median temporal artery Halo Score decreased from 11 to 0, axillary artery Halo Score remained stable. Median Total Vascular Score on FDG-PET/CT reduced from 11.5 to 6.5. In our experience, TCZ showed an excellent response with acceptable safety in GCA, with improvement on US and FDG-PET/CT imaging.